2012
DOI: 10.1177/0969733011429342
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of clinical situations that cause critical care nurses to experience moral distress

Abstract: Little is known about the consequences of moral distress. The purpose of this study was to identify clinical situations that caused nurses to experience moral distress, to understand the consequences of those situations, and to determine whether nurses would change their practice based on their experiences. The investigation used a descriptive approach. Open-ended surveys were distributed to a convenience sample of 204 critical care nurses employed at a university medical center. The analysis of participants' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
155
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(188 citation statements)
references
References 19 publications
(67 reference statements)
3
155
0
8
Order By: Relevance
“…[52][53][54][55][56][57][58] For example, distressed health care providers can experience decreased job satisfaction, [59][60][61] unsettling physical symptoms such as insomnia and headaches, and disruptive psychological symptoms such as loss of confidence and self-worth. 26 Moreover, nurses' moral distress has been associated with absenteeism, burnout, intentions to quit, and leaving the profession. [62][63][64][65] These consequences can lead to inadequate staffing, which in turn, is linked to unfavorable patient outcomes such as hospital-acquired infections.…”
Section: 50mentioning
confidence: 99%
See 2 more Smart Citations
“…[52][53][54][55][56][57][58] For example, distressed health care providers can experience decreased job satisfaction, [59][60][61] unsettling physical symptoms such as insomnia and headaches, and disruptive psychological symptoms such as loss of confidence and self-worth. 26 Moreover, nurses' moral distress has been associated with absenteeism, burnout, intentions to quit, and leaving the profession. [62][63][64][65] These consequences can lead to inadequate staffing, which in turn, is linked to unfavorable patient outcomes such as hospital-acquired infections.…”
Section: 50mentioning
confidence: 99%
“…66 Lingering effects of providers' moral distress can lead to moral desensitization, 50 harmful workplace climates, 23 and suffering of patients and their families. 26 The health system itself is financially affected when moral distress drives nurses and other providers to decrease their work engagement and productivity. 23,59,67,68 …”
Section: 50mentioning
confidence: 99%
See 1 more Smart Citation
“…Moral distress arises when one cannot behave in a way one believes to be ethically correct; it has been well described in nurses, and is particularly common in end-of-life scenarios, particularly when nurses believe treatment to be futile. 19 It can lead to severe physical and emotional 20 Less is known of how physicians experience moral distress; one study found the experience to be more intense but occurring less frequently than in nurses, but did not investigate long-term consequences. 21 However, families also can experience moral distress if there is discordance between their perceptions and those of health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of conflicts on the ICU team manifests as lack of coherence, lower efficiency and quality of work, and irrational behaviour. In some cases, a realisation of the inappropriateness of treatment was a reason for resigning from the profession, both among nurses and physicians [21] and the main cause of moral distress that arouses increasing interest [22,23]. Moreover, the financial consequences of conflicts are important, including costs of legal proceedings, team changes or treatment of complications [24].…”
mentioning
confidence: 99%